اثر بعض قرارات الإنتاج و العمليات في إنتاجية العمل : دراسة استطلاعية لاراء المدراء في مصنع غزل ونسيج الموصل - د. أكرم احمد الطويل; محمد مهيب الدباغ (PROSPECTIVE RESEARCHES, 2023)
This study has aimed at determining the effects of some production and operations decisions in Labor productivity in Mosul Textile Factory. Production and Operations decisions are regarded as the most vital decisions which have a significant role in achieving some of these goals. Some of which is increasing Labor Productivity. And because of the Limitation of the Studies that handled the effective relation between these Variables, especially in the Iraqi, the researchers intended to include this advanced study, to the extents of advantages within a Comprehensive frame in an attempt to study the relation and the impact between them. In general, this study tries to answer the following questions: 1-Is there an obvious perspective for the managers in Mosul textile factory about Production and operations decisions and its Tradeoffs؟ 2-Is there an obvious Perspective for the managers in Mosul textile factory about the concept of Labor Productivity and Some of the factors affecting them? 3-Have the managers in the factory , under the study, an obvious vision about the relation and the effects of Some of the Production and Operations in Labor Productivity . The Study has concluded with a set of Conclusions, the most important of them are : -There is a significant Correlation relation between Production and Operations decisions on Labor Productivity. - There is a significant effects of the production and Operations decisions on Labor Productivity. Basset on the Conclusions of the study, A numbers of recommendations are made depending on them.